The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

المسؤولية الجزائية لمصفي الشركات التجارية - مرجي, نفيسة (Université Abd El Hamid Ibn Badis Mostaganem, 2024)
مــلخص مذكرة الماستر تحتل الشركات التجارية في العصر الراهن أهمية بالغة في بناء وتنمية اقتصاد الدول، بحيث أصبحت تشكل دعامة لاستقرارها الاقتصادي، ولقد حظيت باهتمام المشرع الجزائري فنظم حياة الشركة في مختلف مراحلها بداية من تأسيسها وتسييرها إلى غاية انقضائها . إن الشركة باعتبارها شخصا معنويا تتأسس وتباشر نشاطها لتحقيق الغرض الذي أنشئت من أجله، فإنها معرضة لانقضائها ولحلها لأي سبب من أسباب الانقضاء، فتنتهي الرابطة القانونية التي تجمع بين الشركاء وتدخل في مرحل التصفية

La responsabilité pénale du Capitaine - Nicolopoulos-Salle, Zoé (Aix-Marseille Université, 2019)

L'ordonnance du 2 novembre 2012 portant réforme pénale en matière maritime - Martin, Karine (Aix-Marseille Université, 2013)

L'évolution de la répression pénale de la pollution maritime par hydrocarbures - Monteil, Leslie (Aix-Marseille Université, 2009)

Le droit pénal maritime - Essou, Michel (Aix-Marseille Université, 2004)

La responsabilté pénale du transporteur routier - Garofalo, Ludovic (Aix-Marseille Université, 2004)

Le témoignage des enfants en droit pénal et en droit civil - Dubreuil, Christianne (Université de Montréal, 1990)